اتجاه تغير قرينة الجفاف لديمارتون وعلاقته بتغير درجة الحرارة وكمية الأمطار في محطة اللاذقية خلال الفترة (1968-2008) - قره فلاح, رياض (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف هذا البحث إلى تحديد الإتجاهات السنوية العامة طويلة الأمد، لكل من درجة الحرارة والأمطار بهدف تحديد قيم الإتجاهات السنوية العامة لمعدلات قرينة الجفاف لديمارتون، حيث تم اختيار محطة اللاذقية المناخية. أهم النتائج التي توصل إليها البحث هي وجود تغير في درجة الحرارة في محطة اللاذقية من التناقص بمعدل 0.9 درجة سلسيوس خلال الفترة (1970-1992)، إلى التزايد بمقدار 1.3 درجة سلسيوس خلال الفترة من (1992-2008 )، وإلى حدوث تراجع في معدلات الأمطار خلال الفترة المدروسة بمقدار 5 مم كل سنة، مع ملاحظة عدم وجود تغيير بعد عام 1992، مما أدى إلى حدوث تزايد في معدلات الجفاف. This research aims at assigning the long term annual general trends of both temperature and rainfall in order to determine the general annual trends of Dimarton΄s drought rates presumption during 1968-2008. In this regard, Lattakia's climatic station has been chosen. One of most important results of this research is the existence of real change in the temperature in Lattakia's climatic station from a decrease with a rate 0.9 C˚ during 1970-1992 to an increase with 1.3 C˚ during 1992-2008. The research also shows that there is a decline in rainfall rated 5 mm per year. It is also noted that there is no real change after 1992. This led to a rise in the draught rates according to Dimarton΄s presumption